Placing Antismoking Graphic Warning Posters at Retail Point-of-Sale Locations Increases Some Adolescents' Susceptibility to Future Smoking. Issue 2 (13th December 2017) - Shadel, William G; Martino, Steven C; Setodji, Claude; Dunbar, Michael; Kusuke, Daniela; Lanna, Serafina; Meyer, Amanda
Abstract: Objectives: This experiment tested whether introducing graphic antitobacco posters at point-of-sale (POS) had any effect on adolescents' susceptibility to future cigarette smoking and whether these effects were moderated by adolescents' baseline risk of cigarette smoking. Methods: The study was conducted in the RAND StoreLab, a life-sized replica of a convenience store that was developed to experimentally evaluate how changing aspects of tobacco advertising displays in retail POS environments influence tobacco use risk and behavior during simulated shopping experiences. In this study, 441 adolescents were randomized to one of the four conditions in a 2 (graphic antismoking poster placed near the tobacco power wall: no, yes) × 2 (graphic antismoking poster placed near the cash register: no, yes) experimental design. The outcome of interest was susceptibility to future cigarette smoking. Results: The addition of antismoking posters at POS led to a significant increase in future smoking susceptibility among those adolescents who already were at high risk for smoking in the future ( p < .045). The introduction of graphic antismoking posters had no impact on committed never smokers, regardless of poster location; never smokers' susceptibility to future smoking was uniformly low across experimental conditions. Conclusions: Introducing graphic antismoking posters at POS may have the unintended effect of further increasing cigarette smoking susceptibility among adolescents already at risk.